If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2X + 12 = 68 Reorder the terms: 12 + 2X + 2x = 68 Solving 12 + 2X + 2x = 68 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + 2X + -12 + 2x = 68 + -12 Reorder the terms: 12 + -12 + 2X + 2x = 68 + -12 Combine like terms: 12 + -12 = 0 0 + 2X + 2x = 68 + -12 2X + 2x = 68 + -12 Combine like terms: 68 + -12 = 56 2X + 2x = 56 Add '-2x' to each side of the equation. 2X + 2x + -2x = 56 + -2x Combine like terms: 2x + -2x = 0 2X + 0 = 56 + -2x 2X = 56 + -2x Divide each side by '2'. X = 28 + -1x Simplifying X = 28 + -1x
| 2a+2b-4c=0 | | -3(-10+7x)=-201 | | (x-178)=93384372 | | 3x(x+2)=2x | | n+11(-5n-8)=-4(14n+8) | | -1/3= | | (x-178)=93 | | x^2+200=0 | | 6m(m-2)+3(m^2-7)= | | 4x+1=17-4x | | 2[100-80]-[100-2(50-60)]= | | 3/6= | | 4p+7=2p-2 | | 3(y-1)=6y-4+2y-4y | | 2x(j+17)=j*3x | | 4z+5x-3z+x= | | 50-3y=7y+80 | | -1=-7x+5(3x+11) | | 11(-9b-12)=-6+10(-10b-12) | | 2(-3+x)=10 | | 2x(j+17)=j*x | | -5+2b-4c+6c+10-8b= | | -5x-6=-10-6x | | 37+8x=28-4x | | 2x(7+6)=838 | | 4y-3=8y+25 | | 3b-7=7b+11 | | 2x+2x+24=68 | | 2x(7-6)=838 | | 5x+2-x=-46 | | 2x(7-6)=97 | | 5x+6-9=72 |